Mild Rhodium(III)‐Catalyzed Cyclization of Amides with α, β‐Unsaturated Aldehydes and Ketones to Azepinones: Application to the Synthesis of the Homoprotoberberine Framework1. Issue 20 (16th April 2013) - Shi, Zhuangzhi; Grohmann, Christoph; Glorius, Frank
<x xml:space="preserve">Abstract</x> Seven! The title reaction can be described as an intermolecular annulation involving tandem CH activation, cyclization to give the seven‐membered ring, and condensation steps. Biologically interesting azepinone derivatives can be prepared in this way. The synthetic potential of this method was demonstrated by the construction of the homoprotoberberine ring system.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>